Optimizing Islamic Education Learning through Understanding Students' Learning Modalities in Improving Academic Achievement - Meriyanti, Meriyanti; Rosa Diana, Miska; Suryana, Ermis; Sutarto, Sutarto (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2024)
This research aims to recognize student learning modalities and analyze the implications of learning modalities in optimizing PAI learning, because by recognizing them, students can determine learning styles, teachers can determine learning strategies and methods and parents can educate and treat children according to their respective learning styles. In this research there is David Kolb's learning modality theory, he believes that there are 4 learning styles, namely diverger style, assimilator style, converger style, accommodator style, while Richard Bandler, John Grinder, and Michael Grinder put forward 3 learning styles, namely Visual, Auditory and kinesthetic. This paper uses the library research method, with a qualitative approach, data collection techniques namely documentation, data taken in the form of primary data from articles, books and theses related to the theme of learning modalities and implications in PAI learning and secondary data from the Koran an interpretation. The conclusion is that the implications of learning modalities for optimizing PAI learning are that teachers can determine the learning curriculum, can determine learning resources, can determine learning materials, can choose media that are suitable for students, use varied methods, can carry out assessment strategies and develop student potential, and schools also contribute in providing school facilities.